Karakterisasi Xilanase dari Bakteri Xilanolitik XJ20 asal Tanah Hutan Taman Nasional Bukit Duabelas Jambi Indonesia - INAYAH NOER MAZIDAH; LAKSMI AMBARSARI; ANJA MERYANDINI (Jurnal Sumberdaya Hayati, 2016)
Xylanase is an extracellular enzymes that can be produced by microbes which capable to degrade xylan into xilo-oligosaccharides (XOS) and xylose. Application of xylanase is still not optimal due to the lack of availability of superior microbial cultures producing xylanase. The purpose of this study was to determine the characteristics of xylanase produced by bacteria isolated from Forest land Bukit Duabelas National Park, Jambi, Indonesia. Xylanase produced by bacterial isolate XJ20 was selected for further enzymatic activity and characteritics assays. Xylanolytic activity was measured by using the 3.5-dinitrosalicylic acid (DNS) assay. High activity of xylanase was recorded at three times of incubation, which were 6 (0.015 U/mL), 14 (0.012 U/mL) and 20 (0.007 U/mL). The first peak and the second peak reached the highest activity at a temperature of 70 °C, however, the first peak reached the highest activity at pH 4.0 and a second peak at pH 7.0. pH 4.0 xylanase were incubated at room temperature and 70 °C has a half time consecutive 9 hours and 6 hours, whereas at pH 7.0, has a half time consecutive 4 hours and 3 hours. Stability of enzyme better at pH 4.0 and at room temperature.